THE EFFECTIVENESS OF ONLINE TUTORIAL DISCUSSIONS: PERCEPTIONS FROM MEDICAL STUDENTS - Safira, Nyimas Natasha Ayu; Ekaputri Hz, Tia Wida; Aryanti, Nindya; Puspasari, Anggelia; Maharani, Citra; Enis, Rina Nofri; Tarawifa, Susan; Halim, Rita; Irlianissa, Mutiara (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Tutorial discussions are a form of implementing Problem-Based Learning (PBL) in medical education. Students' cognitive, motivational, and demotivating aspects determine the effectiveness of tutorial discussions. The COVID-19 pandemic has changed learning methods to online learning, and the implementation of online tutorial discussions can affect the effectiveness of discussions. Objective: This study aims to determine the effectiveness of online PBL tutorials at Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi (FKIK UNJA) Method: This is an observational study with a cross-sectional design, 260 students became respondents. Data was collected using a modified Tutorial Group Effectiveness Instrument (TGEI) Results: As many as 51.5% of students rated the implementation of online tutorial discussions as quite effective. Based on cognitive and motivational aspects, > 60% of students rated tutorial discussions as effective, while from demotivation aspects, 85% of students rated discussions as quite effective. Conclusion: The implementation of online tutorial discussions at FKIK UNJA was quite effective. In online tutorial discussions, positive elaborations are still formed among students. Students agree that the success of tutorial discussions is students' responsibility, and irresponsible group members when doing group assignments can reduce the effectiveness of discussions.